Geochemical Evaluation of the Kazhdumi Formation in the Northwest of the Persian Gulf - Sadegh Barati Boldaji; Ebrahim Sfidari; Ehsan Hosseiny; Bijan Nouri; Houshang Mehrabi; Saeed Najari (Journal of Stratigraphy and Sedimentology Researches)
AbstractThe Kazhdumi Formation (Albian) consists of shale to limestone and marl facies, considered as one of the most important source rocks in the north of the Arabian Plate. This study evaluates the geochemistry of the Kazhdumi Formation as a potential source rock in the northwest of the Persian Gulf in the Hendijan, Soroosh, Foroozan, and Kharg fields. For this purpose, Rock-Eval pyrolysis analysis was performed on 140 cutting samples to assess the quantity and quality of organic matter and 53 vitrinite reflectance samples to examine the maturity. The absence of stratification in the water column and unsuitable environmental conditions have not led to the proper preservation of organic matter. Therefore, organic matters are mostly influenced by continental type kerogen (Type III) in this study, ranging from immature to early mature kerogen based on vitrinite reflectance.. However, towards the northeast sector of the Arabian Plate (Hendijan and Kharg fields), due to the presence of organism growth conditions in the water column and the prevailing anoxic conditions at the water-sediment contact (intra-shelf basin), the preservation of organic materials has occurred. The organic matter in this section is mostly marine type (Type II kerogen) and mature based on the vitrinite reflectance data. It seems that the Khafji-Hendijan paleo-high has played an important role in the maturity of the Kazhdumi Formation due to its influence on sediments after the deposition of the Kazhdumi Formation.Keywords: Kazhdumi, Source rock, Persian Gulf, Hendijan, Foroozan  IntroductionThe Persian Gulf is one of the richest sedimentary basins for the production and storage of hydrocarbons in the world. The presence of source rocks with abundant organic materials, reservoirs with carbonate composition, and the presence of suitable cap rocks along with existing traps have led to the accumulation of a large volume of oil and gas in the Persian Gulf. The presence of one-third of the world's gas reserves, indicating the appropriate maturity of source rocks in the depths (Rabbani 2007), and considering the geopolitical and strategic position of the Persian Gulf, further emphasize the importance of research in this region. The early Aptian transgression led to the deposition of Dariyan (Shahbazan) limestones in southern Iran (James and Wynd 1965). Subsequently, a widespread regression in the late Aptian encompassed the region, resulting in a depositional hiatus at the top of the Dariyan Formation. Nevertheless, deposition continued in deeper areas such as the Garau seaway, Kazhdumi intra-shelf basins and the Bab Basin (Sfidari et al. 2016, 2021; Sfidari et al. 2024). During the Albian period, the Arabian Plate acted as a source of clastic sediments for the Burgan Delta (Bordenave and Burwood 1995). The delta previously mentioned has transitioned to deeper, anoxic conditions. Consequently, the sediments of the Burgan Formation have transformed into the Kazhdumi Formation, characterized by marl and black shale facies (Ziegler 2001). In Iranian fields along the shores of the Persian Gulf, such as Hendijan (near the decline of Dezful), the Kazhdumi Formation is mainly composed of shales, marls, and limestones with a small number of sandstones layers in a neritic environment. In the Soroosh, Nowruz, and Foroozan fields, which are further from the Iranian coast, an Arab unit like the Nahar Omar is still used instead of the Kazhdumi Formation. The purpose of this research is to investigate the hydrocarbon potential of the Kazhdumi Formation in the Hendijan, Soroosh, Foroozan, and Kharg fields located in the northwest of the Persian Gulf and evaluate organic-rich sedimentary environments using Rock-Eval pyrolysis and Vitrinite Reflectance. Materials & MethodsThe present study plan evaluates the hydrocarbon generation potential of the Kazhdumi Formation in the Hendijan, Soroosh, Foroozan, and Kharg fields using the results of Rock-Eval 6 pyrolysis and vitrinite reflectance to determine the hydrocarbon production potential. To achieve this goal, 140 samples were chosen for Rock-Eval analyses and 53 samples for vitrinite reflectance analyses. Discussion of Results & ConclusionsMigration index and examination of infected samples: The curve of changes in S1 against the weight percentage of TOC was utilized to evaluate the contamination levels in the samples (Hunt 1996; Behar et al. 2001). Also, PI values above 0.5 are another criterion for the contamination of samples (Hunt 1996). Most of the samples are under the S1/TOC graph slope line, indicating the non-contamination of the samples.Determination of the quantity and potential of the Kazhdumi Formation: The total organic carbon content for the Kazhdumi Formation, generally in the northwest region of the Persian Gulf, varies between 0.2 to 6.24 weight percent. In the Hendijan Field, the TOC content ranges from 0.86 to 6.24 weight percent, indicating an average to excellent quantity, with an average TOC content of 2.93, representing an excellent quantity. The TOC content for the Soroosh Field ranges from 0.2 to 1.66 weight percent, covering a weak to good quantity for the Kazhdumi Formation. In addition, the average TOC value of this formation in the Soroosh Field is 0.8 weight percent, indicating a quantity in the medium range. The TOC values in the Foroozan Field ranged from 0.62 to 1.58 weight percent with an average of 1.20, indicating a medium to good quantity.. The TOC values in the Kharg Field are in the range of 0.62–0.78 weight percent, indicating that the quantity of the Kazhdumi Formation in this field is in the moderate range, (average 0.7). It should be noted that only four samples from the Kharg Field have been studied in this research, which cannot be representative of the entire thickness of the Kazhdumi Formation in this field.Quality and thermal maturity of the Kazhdumi Formation: Hydrogen index values in the Hendijan Field ranges from 309 to 613 (milligrams of hydrocarbon per gram of TOC), indicating a combination of Type I and Type II kerogen for the Kazhdumi Formation. In the Soroosh Field, this parameter ranges from 59 to 333 (milligrams of hydrocarbon per gram of TOC), representing Type III kerogen for most samples. In addition, in the Foroozan Field, the hydrogen index ranges from 133 to 736 (milligrams of hydrocarbon per gram of TOC). Out of the total samples studied, six samples have hydrogen index values below 200 (milligrams of hydrocarbon per gram of TOC), out of the total samples studied.. The remaining samples in this field have values higher than 200 (milligrams of hydrocarbon per gram of TOC), indicating a combination of Type II and III kerogen. Hydrogen index values in the Kharg Field range from 193 to 291 (milligrams of hydrocarbon per gram of TOC), indicating Type III kerogen for the Kazhdumi Formation in this field. The plot of hydrogen index versus oxygen index also confirms the above results.During high relative sea level (Figure 9), a large volume of cold and fresh water containing nutrients entered into the photic zone which led to the expansion of a productive organic zone in the water column. But, in the lower part, the non-oxygen conditions/suboxic zone prevailed. These conditions have led to high sedimentation rates and preservation rates of organic matter at the water-sediment boundary in deeper parts of the sedimentary environment, especially in the intrashelf basin (location of the Hendijan Field). The total organic carbon content and hydrogen index values in the Hendijan Field and to some extent the Kharg Field confirm the mentioned discussions. The shale-rich facies in the upper parts of the Kazhdumi Formation containing Type II kerogen in the Hendijan Field (as the southeastern part of the intrashelf basin) have formed under oxygen-free to suboxic environmental conditions. These conclusions are confirmed by oxygen-depleted conditions reported in the central to northeastern parts of the central Dezful depression (Bordenave and Hegre 2005; Sfidari et al. 2016).At the same time, the southwest of the basin (the location of Foroozan and Soroosh fields) is influenced by the influx of turbulent river waters and no layering state in the water column (by density) has been created.Therefore, as marine organic materials have been relatively degraded due to the dominance of dryness in the upper parts of the Kazhdumi Formation, this part of the formation has been deposited in marine conditions containing oxygen.On the other hand, the interpretation of tectonic factors on events after the deposition of the Kazhdumi Formation provides clear information on the maturity changes of the Kazhdumi Formation from the Foroozan, Soroosh towards the Hendijan fields. It can be concluded that the greater maturity of the Kazhdumi Formation in the Hendijan Field compared to the Foroozan and Soroosh fields is due to the higher thickness of the upper Cretaceous sediments (Sarvak, Ilam, and Gurpi formations) in the northern part of the Hendijan–Khafji Paleo-High.